Recovery From a Myocardial Infarction Is Impaired in Male C57bl/6 N Mice Acutely Exposed to the Bisphenols and Phthalates That Escape From Medical Devices Used in Cardiac Surgery. (6th November 2018) - Shang, Jijun; Corriveau, Jeanne; Champoux-Jenane, Alexandre; Gagnon, Julie; Moss, Emmanuel; Dumas, Pierre; Gaudreau, Eric; Chevrier, Jonathan; Chalifour, Lorraine E
Abstract: Bisphenols and phthalates leach from medical devices, and this exposure is likely to increase in postcardiac surgery patients. Previous studies suggest that such chemical exposure may impact recovery and wound healing, yet the direct effects of bisphenols and phthalates are unknown in this context. To study the direct effect of clinically based chemical exposures, we measured the metabolites representative of 6 bisphenols and 10 phthalates in men before and after cardiac surgery and then replicated this exposure in a mouse model of cardiac surgery and assessed survival, cardiac function and inflammation. Bisphenol A (BPA), di-ethyl hexyl phthalate (DEHP), butylbenzyl phthalate, di-isodecyl phthalate, and di- n -butyl phthalate metabolites were increased after surgery. DEHP exposure predominated, was positively correlated with duration on the cardiopulmonary bypass machine and exceeded its tolerable daily intake limit by 37-fold. In vivo, C57bl/6 N male mice treated with BPA+phthalates during recovery from surgery-induced myocardial infarction had reduced survival, greater cardiac dilation, reduced cardiac function and increased infiltration of neutrophils, monocytes and macrophages suggesting impaired recovery. Of interest, genetic ablation or estrogen receptor beta (ERβ) antagonism did not improve recovery and replacement of DEHP with tri-octyl trimellitate or removal of BPA from the mixture did not ameliorate these effects. To examine the direct effects on inflammation, treatment of human THP-1 macrophages with BPA and phthalates induced a dysfunctional proinflammatory macrophage phenotype with increased expression of M1-type macrophage polarization markers and MMP9 secretion, yet reduced phagocytic activity. These results suggest that chemicals escape from medical devices and may impair patient recovery.